2020
DOI: 10.1177/2325967120915698
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction in Patients Older Than 50 Years: A Systematic Review and Meta-analysis

Abstract: Background: There is no consensus regarding the best treatment approach for middle-aged patients with anterior cruciate ligament (ACL) injuries. Chronic ACL-deficient knees are often associated with instability as well as secondary meniscal and cartilage lesions. ACL reconstruction (ACLR) has achieved satisfactory outcomes in younger patients; however, the effectiveness and safety of ACLR in middle-aged patients remain uncertain. Purpose: To compare the patient-reported functional scores, arthrometric outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…However, this prior meta-analysis was unable to assess for differences in complication rates due to their low incidence after ACL reconstruction and the limited number of patients included in the analysis. Compared with the study by Tan et al., 21 the current study highlights this difference in complication rates, with the most notable difference being the rate of DVT/PE in older patients.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…However, this prior meta-analysis was unable to assess for differences in complication rates due to their low incidence after ACL reconstruction and the limited number of patients included in the analysis. Compared with the study by Tan et al., 21 the current study highlights this difference in complication rates, with the most notable difference being the rate of DVT/PE in older patients.…”
Section: Discussioncontrasting
confidence: 70%
“…A recent meta-analysis including four retrospective cohort studies and a total of 287 patients (129 older than 50 years, 158 younger than 50 years) found no difference in the improvement of International Knee Documentation Committee scores or Lysholm scores between patients older than and younger than 50 years old. 21 There was also no difference in Tegner activity scores or the incidence of knee AP laxity as measured on KT-1000 or KT-2000 arthrometer at final followup. 21 All studies included in the meta-analysis reported AGE IMPACTS COMPLICATIONS AFTER ACLR e5 significant improvement in clinical outcomes across both patient age groups.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…There is considerable controversy surrounding the role for surgery in older patient populations with ACL tears [3, 8, 9, 30, 31, 35, 37, 38]. Patients under the age of 40 who undergo nonsurgical management of these injuries are at increased risk of sustaining subsequent meniscal and chondral injuries and may develop knee osteoarthritis at a higher rate than those who receive ACLR [3, 10, 17, 18, 22, 23].…”
Section: Discussionmentioning
confidence: 99%